2017
DOI: 10.1111/jac.12252
|View full text |Cite
|
Sign up to set email alerts
|

Biochar amendment of fluvio‐glacial temperate sandy subsoil: Effects on maize water uptake, growth and physiology

Abstract: Coarse sandy soils have poor water retention capacity, which may constrain crop growth during drought. We investigated the effect of biochar amendment to subsoil on crop physiological processes and maize yield, comparing irrigated and drought conditions. A two‐year greenhouse experiment was conducted with one‐time application of straw biochar at concentrations of 0%, 1%, 2% and 3% (B0, B1, B2 and B3). Maize was planted twice in the same large pots one week and again 12 months after biochar application. Plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Sandy soils are characterised by low water holding capacity and excessive drainage below the root zone (Andry et al, 2009) and therefore considered marginal for agricultural production especially in dry areas. Nevertheless, many hundred thousands of hectares of this soil type formed by glacial river deposits is under cultivation in north-western Europe (Andersen and Aremu, 1991;Andersen et al, 1992;Ahmed et al, 2018). In coarse sand, lack of soil structure, low moisture content, greater bulk density and low organic content tend to increase the mechanical impedance to root growth (Bruun et al, 2012;Wernerehl and Givnish, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sandy soils are characterised by low water holding capacity and excessive drainage below the root zone (Andry et al, 2009) and therefore considered marginal for agricultural production especially in dry areas. Nevertheless, many hundred thousands of hectares of this soil type formed by glacial river deposits is under cultivation in north-western Europe (Andersen and Aremu, 1991;Andersen et al, 1992;Ahmed et al, 2018). In coarse sand, lack of soil structure, low moisture content, greater bulk density and low organic content tend to increase the mechanical impedance to root growth (Bruun et al, 2012;Wernerehl and Givnish, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The biochar induced benefits include reduced nutrient leaching from amended soils (Laird et al, 2010;Bakshi et al, 2014), increased soil nutrient availability (Xu et al, 2015), crop nutrient uptake (Madiba et al, 2016), and fertilizer use efficiency (Wang et al, 2017). Furthermore, increased soil water retention (Bruun et al, 2014) has been shown to improve plant productivity (Xu et al, 2015;Ahmed et al, 2018). However, neutral or negative effects of biochar addition have also been reported (Deenik et al, 2010;Reibe et al, 2015;Kolton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, neutral or negative effects of biochar addition have also been reported (Deenik et al, 2010;Reibe et al, 2015;Kolton et al, 2017). The results vary for different experimental conditions (Spokas et al, 2012), such as biochar type (Crane-Droesch et al, 2013) and biochar application rate (Liu et al, 2013) as well as crop species (Ahmed et al, 2018). Negative effects on potato growth have been related to reduced uptake of phosphorus (P) and nitrogen (N) as well as the release of ethylene from fresh biochar, which, however, is considered to be a short lived and transient effect (Spokas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has high carbon content, rich pore structure, large specific surface area, various organic functional groups contained (or absorbed) on the surface, strong ion exchange adsorption capacity and stable physicochemical properties. Biochar addition to sandy soil was considered to improve a range of soil physical and hydraulic properties including soil bulk density (Githinji, 2014;Suliman et al, 2017;Ahmed et al, 2018), soil hydraulic conductivity (Uzoma et al, 2011;Ibrahim et al, 2013;Barnes et al, 2014;Jacka et al, 2018), water infiltration rate (Ibrahim et al, 2013;Githinji, 2014), soil hydrophobicity (Ibrahim et al, 2013), soil water holding capacity (Dugan et al, 2010;Karhu et al, 2011;Devereux et al, 2012;Suliman et al, 2017;Al-Wabel et al, 2018), and soil available water (Baronti et al, 2014;Bruun et al, 2014;Glab et al, 2016;Hansen et al, 2016), as well as crop properties including crop production ( Faloye et al, 2017;She et al, 2018), water use efficiency (Xiao et al, 2018) and crop drought resistance (Poormansour and Razzaghi, 2018). The application of biochar improves the physical and hydraulic characteristics of sandy soil (Karhu et al, 2011) and has direct effects on soil water movement.…”
Section: Introductionmentioning
confidence: 99%